Two-Dimensional Tannin Fingerprints by Liquid Chromatography Tandem Mass Spectrometry Offer a New Dimension to Plant Tannin Analyses and Help To Visualize the Tannin Diversity in Plants - Juha-Pekka Salminen (AMER CHEMICAL SOC, 2025)
Tannins are large-molecular-weight plant polyphenols that are produced in fruits, berries, leaves, flowers, seeds, stems, and roots of woody and non-woody plants. Hundreds and thousands of individual tannin structures are consequently found in many kinds of natural food and feed products. The huge structural variability in tannins is reflected as vast bioactivity differences between them but not in the accuracy of their typical analysis methods. Here, I show how the modern liquid chromatography mass spectrometry methods can be used to obtain new types of two-dimensional tannin fingerprints to better visualize both the tannin content and diversity in plants with just one 10 min analysis per sample.